Dobroczynność względem sierot na ziemiach polskich do 1918 roku - Domańska, Joanna (Biuletyn Historii Wychowania, 2011)
Since the baptism of Poland up to 1918, the social care of orphans was diversified. Until the annexations, the care of parentless children in the Polish territories had been environmental and stemmed from voluntary and charitable actions taken up mostly by the Church. The creation of children wards in hospitals and shelters, and the establishment of children’s households in Warsaw as a result of father G. Baudounin’s initiative, might be considered as prototype actions in the complete institutional care of orphaned children. However, during the time of annexations, the situation of orphans became significantly diversified because it depended on the invaders’ policy and the citizens’ activity. Thus, on the one hand, it was created by the occupying country, on the other, it was shaped by tradition. In the territories of each of the conquerors there were periods of liberalization of law, which rendered it possible, at least to some degree, to follow Polish concepts. These were mostly based on philanthropy, charity religious groups, associations and individuals. It needs to be stated that at the beginning of the 21st century, in all of the partitioned territories, the orphanages were governed by obsolete regulations although tried out in other countries. In each of the annexed parts of Poland, the educational and caring actions stemmed from the acquired legislative system. Under the Austrian occupation it was the commune that had the duty of taking care of the parentless children as it was stated in the act passed on 3rd December 1863. In the Prussian part of Poland, the commune’s duty of taking care of the orphans was stated in the act passed in July 1870. It is worth mentioning that the legislative in Prussia was very similar to the Austrian one. The only difference between them was their effectiveness – it was far more efficient in the Prussian province. Under the Russian invasion the regulations concerning the orphanages were quite different. Since the resolution from 1817, the public care of orphans relied on the good will of the society. It was not until the ruling from 1870 that the city councils of public philanthropy, supervising such institutions, were brought to life. At the turn of the 19th century in Poland, especially among social and educational activists, the problem of children’s care became more popular. The necessity of providing care through social actions based on the law was discerned. During World War I, the problem of orphanhood achieved a new dimension, the so-called war orphanhood. It was not effectively taken care of until the end of the war.